THE INFLUENCE OF TASTE ON CONSUMER LOYALTY OF MICKEY DIMSUM WITH PURCHASE DECISIONS AS AN INTERVENING VARIABLE (CASE STUDY ON MICKEY DIMSUM KP. DURIAN TEBING TINGGI CUSTOMERS) - Cai Cen, Cia (International Conference on Health Science, Green Economics, Educational Review and Technology, 2020)
This study aims to determine "The Effect of Taste on Mickey Dimsum Consumer Loyalty With Purchase Decisions As Intervening Variables (Case Study on Mickey Dimsum Customers Kp. Durian Tebing Tinggi)". The method of determining the sample used in this study is to use the Cochran formula as many as 96 samples which are Mickey Dimsum Kp consumers. High Cliff Durian. Based on the results of the analysis of hypothesis 1, it can be concluded that the first hypothesis is accepted, meaning that the Taste variable (X) affects the Purchase Decision variable (Z). Based on the results of the analysis of hypothesis 2, it can be concluded that the second hypothesis is accepted, meaning that the Taste (X) variable affects the Customer Loyalty variable (Y). Based on the results of the analysis of hypothesis 3, it can be concluded that the third hypothesis is accepted, meaning that the Purchase Decision variable (Z) has affected the Consumer Consumer Loyalty (Y). Based on the results of the analysis of hypothesis 4, it shows that the indirect effect of the Taste variable (X) on Consumer Loyalty (Y) through Purchase Decision (Z) is bigger than the direct effect of the Taste (X) variable on Consumer Loyalty (Y).